Factors Influencing the Economic and Social Prosperity of Aboriginal Peoples - Rose, Sara M.; Rose, Wade R. (Journal of Aboriginal Economic Development, 2012)
Numerous historical and current factors have combined to influence the economic and social prosperity of Aboriginal peoples. This paper reviews the contrary governmental and Aboriginal perspectives of the history of the last few hundred years and provides an overview of the current situation in Aboriginal communities in North America. This is followed by a discussion of economic and social development factors taken from qualitative and quantitative studies found in the literature. Conclusions and suggestions for future research are provided.